2019
DOI: 10.1111/papr.12822
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique Using Magnetic Resonance Imaging in the Supine and Prone Positions for Diagnosing Lumbar Adhesive Arachnoiditis: A Preliminary Study

Abstract: BackgroundLumbar adhesive arachnoiditis is a debilitating neuropathic condition and is difficult to diagnose owing to lack of definitive diagnostic criteria. By focusing on the intrathecal mobility of nerve roots, we assessed whether useful diagnostic criteria could be established using MRI.MethodsSeventeen patients with a high risk for lumbar adhesive arachnoiditis and 18 no‐risk patients with chronic low back pain and/or leg pain participated in this study. The patients underwent MRI in both the supine and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…No preference towards a certain level of the spinal column was observed either. Tsuchida et al [ 51 ] searched for new MRI diagnostic criteria that could make it possible to diagnose CSAA in earlier and asymptomatic stages of the disease. Reduced nerve root mobility has been suggested as an early marker for the development of CSAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No preference towards a certain level of the spinal column was observed either. Tsuchida et al [ 51 ] searched for new MRI diagnostic criteria that could make it possible to diagnose CSAA in earlier and asymptomatic stages of the disease. Reduced nerve root mobility has been suggested as an early marker for the development of CSAA.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the hypothesis, that a high-dose cortisone treatment is most effective in early stages of the disease because it intervenes in the pathomechanism and therefore interrupts the development of the adhesions and all following complications. To make early diagnosis possible, it is necessary to discover diagnostic criteria for the early stages of the disease, such as the reduced mobility of the nerve roots in high-risk patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…with low back pain without AA), those with AA exhibited large, low density, non-mobile, dorsally clumped roots that failed to migrate ventrally [ Table 1 ]. [ 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to mention that only a third of patients included in the present study had gadolinium‐based contrast enhancement during imaging. Another recent study found that MRI in supine and prone positions could facilitate the early detection of lumbar adhesive arachnoiditis 9 . Further studies could assess the impact of using contrast agents and multimodal MRI on diagnostic findings.…”
mentioning
confidence: 99%
“…Another recent study found that MRI in supine and prone positions could facilitate the early detection of lumbar adhesive arachnoiditis. 9 Further studies could assess the impact of using contrast agents and multimodal MRI on diagnostic findings.…”
mentioning
confidence: 99%